INFLUENCE OF LOADING AND UN LOADING TIME ON FUNCTIONING COMPLEX OF MICROSYSTEMS IN TRANSIT FREIGHTS PUBLIC MOTOR TRANSPORT - E. Е. Vitvitskiy; E. S. Fedoseenkova (Вестник СибАДИ)
In the article, they were tested for compliance with the modern practice of representing the theory of freight road transport on the effect of downtime when performing loading and unloading operations for the production of motor vehicles. The solution of the problem is represented by the example of transportation of reinforced concrete products from a plant in the city in the aggregate of micro motor transport systems by rolling stock of general use. Calculated by the dependence of the output in tons and ton-kilometers for the totality of micro motor transport systems.